KODE ETIK JURNALISTIK DAN INDEPENDENSI PRODUKSI PROGRAM TELEVISI INVESTIGASI - Suwadi Suwadi (Avant Garde, 2019)
This study aims to determine and explain about the importance of the Kode Etik Jurnalistik (KEJ) used in producing television programs, including a program of investigation. The issue of the code of conduct associated with the ethical values underlying a production, and it is necessary so that a television program has the responsibility for the moral good. The object of this research is investigation television program of Sigi in Surya Citra televisi (SCTV) with regard to the Kode Etik Jurnalistik (KEJ) statutes of the Press Council (Dewan Pers), Article 2, Article 3,Article 4 and Article 5 of the current stage of reporting, script writing and editing. This study uses the theory of social responsibility equipped with a concept of the Independence by Mc Quail that opinion, accuracy, juxtaposition and Sensationalism. Research studies using qualitative methods of interviews and observation as a data collection tool. In-depth interviews conducted with informants of the production crew Sigi. Participatory observation was done to see the activity of production Sigi editor. This study found the program Sigi still there is a discrepancy with the code of Journalistic ethics on the stage of the coverage article 2, point c is not a bribe while another stage is in conformity with the provisions of articles 2,3,4 and 5 of the Kode Etik Jurnalistik (KEJ). The independence of the indicator of the opinion there is no element of opinion, accuracy indicator there are elements accurately in the reporting and writing of the manuscript, an indicator of Juxtaposition include an element of juxtaposition in writing of the manuscript, an indicator of sensationalism there is an element on the coverage and editing. To avoid the impact of short-term and long-term broadcasters (SCTV) should provide training on crew production news for the Kode Etik Jurnalistik (KEJ) because the value of ethics in a television production is very necessary and should be understood by the journalists involved in the production process. The application of the ethical values embodied in the code of conduct to be a manifestation of the independence of the media in the middle of attraction with a variety of interests that may occur in the production process of a television program such as investigation.